2014
DOI: 10.1111/1346-8138.12721
|View full text |Cite
|
Sign up to set email alerts
|

Association between psoriasis and leisure‐time physical activity: Findings from the National Health and Nutrition Examination Survey

Abstract: Despite evidence that physical activity can reduce the cardiometabolic risk of patients with psoriasis, these patients may engage in less physical activity than those without psoriasis. The aim of this study was to examine the association of the extent of psoriatic skin lesions with the likelihood of participating in leisure-time moderate to vigorous physical activity (MVPA) and metabolic equivalent task (MET)-minutes of MVPA amongst those who participated. The National Health and Nutrition Examination Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Sedentary lifestyle and psoriasis can also be closely connected [ 28 ]. Indeed, according to the 2003–2004 and 2005–2006 NHANES dermatology questionnaires [ 29 ], psoriatic patients are reluctant to engage in physical activities where their skin disease may be visible to others. Thus, in addition to genetic and immune-mediated mechanisms, behavioural factors may have an additional role in explaining the association between obesity and psoriasis.…”
Section: Obesity and Psoriasismentioning
confidence: 99%
“…Sedentary lifestyle and psoriasis can also be closely connected [ 28 ]. Indeed, according to the 2003–2004 and 2005–2006 NHANES dermatology questionnaires [ 29 ], psoriatic patients are reluctant to engage in physical activities where their skin disease may be visible to others. Thus, in addition to genetic and immune-mediated mechanisms, behavioural factors may have an additional role in explaining the association between obesity and psoriasis.…”
Section: Obesity and Psoriasismentioning
confidence: 99%
“…The therapeutic guidelines include the use of topical steroids, topical vitamin D, systemic immunosuppressants and various biologics, such as antitumour necrosis factor (TNF) α, anti-interleukin (IL)-23 and anti-IL-17 antibodies (6)(7)(8)(9)(10)(11)(12)(13)(14). However, treatment adherence and the quality of life of the affected patients are generally very low (1,(15)(16)(17)(18)(19)(20). Recent genome-wide association studies have identified many susceptibility loci for psoriasis and pustular psoriasis, including HLA-C*06:02, LCE3D, IL23R, CARD14 and IL36RN (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…4 However, this topic still presents some controversial aspects since discrepant studies are available. 5,6 In order to obtain further evidences, we evaluated the impact of regular agonistic physical activity on psoriasis in soccer players of the Italian second league. Particularly, an observational cross-sectional investigation was conducted by analysing a group of 323 Italian second league soccer players (consecutively enrolled during medical check-up at training sessions) and 357 sex, age and body mass index matched controls (chaperones of patients attending the outpatient clinic of Department of Dermatology and Department of Allergy and Clinical Immunology, University of Naples Federico II) from July 2015 to May 2016.…”
mentioning
confidence: 99%
“…Rossi, 2 A. Balato, 1 C. Matucci-Cerinic, 3 F. Braconaro, 4,5 F. Prignano, 3 G. Monfrecola, 1 N. Balato, 1 A. De Paulis 2,4 1 Department of Dermatology, University of Naples Federico II, Naples, Italy, 2 Department of Translational Medical Sciences (DiSMeT), University of Naples Federico II, Naples, Italy, 3 Section of Dermatology, Department of Surgery and Translational Medicine, University of Florence, Florence, Italy,4 Antidoping Federal Commission and Health Protection of "Federazione Italiana Giuoco Calcio", Rome, Italy,5 Medical and Scientific Commission of the National Professional League "Serie B", Rome, Italy Characteristics of Italian second league football players and control subjects…”
mentioning
confidence: 99%